Experimental determination of enrichment of uranium material by gamma-spectroscopic technique - Loat, Bui Van; Anh, Le Tuan; Tam, Nguyen Cong; Khue, Pham Duc; Hue, Bui Minh (VNU Journal of Science: Mathematics - Physics; Vol 29 No 2, 2013)
Abstract: During the last years, as the international illicit traffic of radioactive/ fissionable materials have increased, it became important to be able to apply fast reliable methods for the uranium enrichment determination. In order to determine the uranium enrichment the activity ratios of 234 U/ 235 U and 238 U/ 235 Uwas measured. Uranium isotopic abundance can be determined by alpha spectrometry and mass- spectrometry methods, which are destructive methods. In this work the non-destructive gamma – spectroscopic method for uranium enrichment is presented. The method is applicable to material of any physical form and geometrical shape, and does not require the use of reference materials nor the use of an efficiency calibrated geometry. The activity 234 U/ 235 U was determined by using intrinsic efficiency calibration. The 63.29 keV photopeak of 234 Th and 58.57 keV of 231 Thwere used for determination of activity 238 U/ 235 U. As a test of this method, a highly enriched uranium standard was measured, the obtained result was in agreement with the estimated value. Keywords: Uranium enrichment, gamma-spectrometry, intrinsic efficiency calibration, MGA method.